1. The problem statement, all variables and given/known data Find the inverse of AB if A^(-1)= [4,0;-2,2] and B^(-1)=[-2,0;-2,3]. (See below for picture/additional information.) 2. Relevant equations Inverse of AB = inverse of A*inverse of B 3. The attempt at a solution Using above equation: (AB)^(-1) = [4,0;-2,2]*[-2,0;-2,3] = [-8,0;0,6] I don't understand why this is wrong. I calculated it by hand, and then used two different online matrix calculators when I was told it was wrong. The calculators agree with me. Am I entering it incorrectly? Here is a picture of the "full" question: http://imgur.com/foTsK2e. Thanks.